SF3B1 as a Diagnostic and Prognostic Factor in Iraqi Patient with Chronic Lymphocytic Leukemia - Iqbal Muaafi Abdullah, Yaseen M.Taher, Alaa Fadhel Alwan, Mohammed Maaruf Al-Ani, (Pakistan Journal of Medical & Health Sciences, 2022)
An appropriate prognostic marker is crucial to evade cancer for a better prognosis and better life outcome and to raise the survival rate. The genesis of chronic lymphocytic leukemia has been linked to mutations in specific genes, such as SF3B1. A high rate of splicing factor 3 B1 mutation (SF3B1mut) has been linked to poor prognosis or treatment sensitivity in some forms of cancer.Thirty patients were grouped according to the first diagnosis, the staging of the CLL, follow-up examinations to measure their exposure to Rituximab after 3-6 months of treatment, and to the excluding criteria another Thirty healthy volunteers age and gender-matched were utilized as a control group.The mean age between study and control groups was (61.0 ± 10.7 vs. 59.8 ± 9.7 years); also, the male to female ratio was 2:1 in the control and CLL group, with no significant difference between both groups. Stage II was the most common type of CLL (53.3%), followed by III (35%) and stage IV (10%).SF3b1 was shown to be negative in all study groups, both (after ; before chemotherapy) and control group.